The Role of Notaries in Civil Agreements Legality and Validity of Deeds - Sari, Ratih Mega Puspa; Iskandar PP, Agus; Lumingkewas, Cindy Sandra; Mariani, Mariani (Jurnal Hukum dan Keadilan, 2025)
This study aims to analyze the role of notaries in ensuring the legality and validity of deeds as legal instruments in civil agreements. The main focus of this study is how notaries through their authority in making authentic deeds can provide legal protection and create legal certainty for the parties who agree in civil legal relations. The method used is the normative legal research method with a statute approach, a conceptual approach, and a case approach. Data were obtained from primary legal materials such as laws and court decisions, secondary legal materials in the form of literature and scientific articles, and tertiary legal materials as a complement. Data collection techniques were carried out through literature studies and analyzed descriptively-qualitatively. The results of the study show that notaries play a vital role in ensuring the formal and material validity of an agreement through the authentic deeds they make. Notaries not only act as public officials who record the will of the parties, but also as guardians of professionalism, integrity, and legal order in society. Therefore, enforcement of professional standards and supervision of notarial practices are important in ensuring that notarial functions run in accordance with the principles of justice and legal certainty